Some Properties of Curvature Tensors and Foliations of Locally Conformal Almost Kähler Manifolds - Ntokozo Sibonelo Khuzwayo; Fortuné Massamba (International Journal of Mathematics and Mathematical Sciences)
We investigate a class of locally conformal almost Kähler structures and prove that, under some conditions, this class is a subclass of almost Kähler structures. We show that a locally conformal almost Kähler manifold admits a canonical foliation whose leaves are hypersurfaces with the mean curvature vector field proportional to the Lee vector field. The geodesibility of the leaves is also characterized, and their minimality coincides with the incompressibility of the Lee vector field along the leaves.